Removal of PVA from textile wastewater using modified PVDF membranes by electrospun cellulose nanofibers - Marwa S. Shalaby; Frank Lipnizki; Heba Abdallah; Ahmed M. Shaban; Rania Ramadan; Eman Mansor; Marwa Hosney; Akhil Thomas; Binny Maria Babu; K. E. Merin Rose; Hanna J. Maria; Sabu Thomas (Applied Water Science)
Abstract The objective of this study was to assess the feasibility of using a poly(vinylidene fluoride) (PVDF) membrane modified with cellulose/nanostructures as a separation technique for the removal of poly(vinyl alcohol)(PVA)/reactive dyes from synthetic textile wastewater. The goal was to recycle PVA/reactive dye yellow 145 for reuse in the industry while simultaneously reclaiming water for reuse. To achieve this, the study aimed to evaluate the influence of SnO2/ZnO nanostructures on the polymer mixture, examining their impact on permeation and rejection of PVA/reactive dye. Additionally, the study investigated the antifouling properties of PVDF, both in the presence and absence of electrospun cellulose nanofibers. Chemical analysis techniques, including SEM, EDS, FTIR, mechanical strength testing, contact angle measurement, AFM, and determination of molecular weight cutoff (MWCO), were employed to assess the synthesized membranes. The MWCO results indicated a decrease in pore size after surface modification with electrospun cellulose acetate (CA), with the modified membrane (M2-Mod) showing a reduced MWCO of 6700 Da compared to the unmodified membrane’s MWCO of 13,980 Da. Furthermore, the study aimed to identify the optimal polymeric nanocomposite of PVDF with nano-SnO2 or ZnO, along with electrospun cellulose nanofibers, to enhance %PVA and %dye rejection while improving membrane productivity and fouling resistance. The formulation containing a mixture of SnO2 and ZnO, in the presence of electrospun CA, demonstrated superior performance, achieving 98% PVA rejection, 95% reactive dye rejection, and a stable flux of 20 LMH, with a normalized flux of 92%. Overall, it can be concluded that the optimized modified membrane formulation (M2-Mod) exhibited excellent antifouling behavior, holding significant potential for promoting circular economy and sustainability in textile wastewater treatment.